The company I keep my life in beauty - Lauder, Leonard A. (New York Harper Business, 2020)
In his much-anticipated memoir, The Company I Keep: My Life in Beauty, Chairman Emeritus and former CEO of The Estě Lauder Companies Leonard A. Lauder shares the business and life lessons he learned as well as the adventures he had while helping transform the mom-and-pop business his mother founded in 1946 in the family kitchen into the beloved brand and ultimately into the iconic global prestige beauty company it is today.
Includes bibliographical references and index.
Keywords: Lauder, Estée.